2018
DOI: 10.1007/s10902-018-9963-5
|View full text |Cite
|
Sign up to set email alerts
|

How Psychological Capital Mediates Between Study–Related Positive Emotions and Academic Performance

Abstract: Abstract:The present study, based on broaden-and-build theory, examines the relationship between study-related positive emotions and academic performance, and the mediating role of psychological capital in this relationship. A sample of 639 Chilean high school students between 14 and 17 years old was used. Through structural equation modelling (SEM), -as hypothesized-a statistically significant indirect effect was found between study-related positive emotions and academic performance via psychological capital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 52 publications
9
94
1
7
Order By: Relevance
“…However, of note was that the strength of associations in the current study (r = .59-.76) which were moderate to high [61], were generally higher than those reported in previous studies that examined the inter-correlations of HERO of r = .15-.63 [21] and r = .46-.61 [23] in youth. This finding could be due to the higher reliability of scales used in our study, i.e., Cronbach's alphas of .85-.94, compared to Cronbach's alphas of .60-.83 [21] and Omega coefficients of .67-.77 [27], or it may suggest the strength of associations is culturespecific. A further alternative explanation could be that strength of associations are age-specific as our study comprised a younger age group (9-14 year, Mage = 11.34), compared to previous studies (e.g., [14-17, 21, 23]).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…However, of note was that the strength of associations in the current study (r = .59-.76) which were moderate to high [61], were generally higher than those reported in previous studies that examined the inter-correlations of HERO of r = .15-.63 [21] and r = .46-.61 [23] in youth. This finding could be due to the higher reliability of scales used in our study, i.e., Cronbach's alphas of .85-.94, compared to Cronbach's alphas of .60-.83 [21] and Omega coefficients of .67-.77 [27], or it may suggest the strength of associations is culturespecific. A further alternative explanation could be that strength of associations are age-specific as our study comprised a younger age group (9-14 year, Mage = 11.34), compared to previous studies (e.g., [14-17, 21, 23]).…”
Section: Discussioncontrasting
confidence: 90%
“…This novelty of HERO's collective predictive benefit was obtained in the context of findings that are consistent with prior studies, whereby the individual constructs were related (H1) [21,23]. However, of note was that the strength of associations in the current study (r = .59-.76) which were moderate to high [61], were generally higher than those reported in previous studies that examined the inter-correlations of HERO of r = .15-.63 [21] and r = .46-.61 [23] in youth.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Academic emotions are a kind of nonintellectual factor closely related to the teaching and learning process, which play an important role in students' learning processes. Many studies have found that academic emotions affect students' psychological flexibility, self-regulated learning, and academic performance [22][23][24], of which positive academic emotions can enhance intrinsic motivation [25] and predict students' academic performance [26], while negative academic emotions predict negative academic performance [27]. In addition, academic emotions also affect students' mental health and, thus, students' subjective well-being [28].…”
Section: Subjective Well-being and Academic Emotionsmentioning
confidence: 99%
“…In academic environments, personal resources (e.g., intrinsic motivation, efficacy perception, etc.) would then relate to how students face demands (e.g., workload) and represent a source of well-being and success themselves (Carmona-Halty, Salanova, Llorens, & Schaufeli, 2018). Even though the number of studies focused on students' resources and personal strengths that lead them to face their academic demands successfully is increasing (e.g., Salanova, Martínez, Bresó, Llorens, & Grau, 2005;Schaufeli & Taris, 2014), according to White et al (2017) the D-R model has been scarcely applied to university students (e.g., Barr, Sessa, Summer, & Bragger, 2015;Mokgele & Rothman, 2014).…”
Section: The Demands-resources (D-r) Model Applied To the Educationalmentioning
confidence: 99%